PEMANFAATAN JAMUR (FUNGI) SEBAGAI BIOINDIKATOR DALAM BIOMONITORING PENCEMARAN TANAH - Oktavita Wulandari; Windi Aulia Putri; Slamet Mardiyanto Rahayu (Nusadaya Journal of Multidiciplinary Studies, 2025)
Soil pollution is an environmental problem caused by hazardous substances such as heavy metals that can damage ecosystems. One method used to monitor soil conditions is biomonitoring using organisms as bioindicators. Fungi have the potential as bioindicators due to their ability to respond to environmental changes through variations in growth and community diversity. This study aims to determine the role of fungi as bioindicators in soil pollution biomonitoring using a literature review method. Data were collected from various scientific sources and analyzed descriptively. The results show that soil pollution reduces fungal diversity and leads to the dominance of more tolerant species. In addition, fungi can absorb and accumulate heavy metals through biosorption. Therefore, fungi are effective bioindicators for assessing soil pollution levels.